Global, regional, and national burden of tracheal, bronchus, and lung cancer attributable to ambient particulate matter pollution among adults aged 70 and above in 1990–2021 and projected to 2044 - Ke-Jie He; Haitao Wang; Jianguang Xu; Guoyu Gong (Frontiers in Public Health)
BackgroundTracheal, bronchus, and lung (TBL) cancer attributable to ambient particulate matter pollution (APMP) is a growing global health concern, particularly in individuals aged 70 and above. This study aims to evaluate past trends, identify key drivers, and project future disease burden.MethodsData from the Global Burden of Disease Study 2021 was analyzed for TBL cancer-related disability-adjusted life years (DALYs) and mortality from 1990 to 2021, stratified by SDI regions. Statistical methods, including Joinpoint regression, age-period-cohort modeling, and decomposition analysis, were used to identify temporal trends and drivers of DALYs. Future projections were made using the Nordpred model.ResultsFrom 1990 to 2021, global DALYs of TBL cancer due to APMP increased steadily (AAPC 0.75%). Population growth was the main driver, accounting for 79.37% of the increase, with epidemiological factors playing a varying role across regions. The highest DALY growth was observed in middle SDI regions (AAPC 2.99%), while high SDI regions saw a decline (AAPC −1.76%). Projections up to 2044 suggest a substantial increase in DALYs across all SDI regions, with the fastest growth expected among individuals aged 70–74, but DALY rates are projected to decline steadily.ConclusionPopulation growth is the primary factor driving the increase in DALYs associated with TBL cancer, with significant regional disparities. Projections suggest a continued rise in disease burden, particularly in lower SDI regions, underlining the urgency for targeted public health interventions and strategies to mitigate exposure and improve healthcare outcomes for at-risk populations.